2013
DOI: 10.2478/s11756-013-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, anticancer and genotoxic properties of α-pinene on N2a neuroblastoma cells

Abstract: α-Pinene, an organic monoterpene, is found in essential oils of pine and coniferous trees. To date, although various biological activities of α-pinene have been demonstrated, its neurotoxicity has never been explored. Therefore in this study, we aimed to describe in vitro antiproliferative and/or cytotoxic properties by 3-(4,5-dimetylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test, genotoxic damage potentials by single cell gel electrophoresis, and oxidative effects by total antioxidant capacity (TAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…In addition to oxidative stress, previous studies reported that different mechanisms have been linked to plant products' cytotoxicity, including: (i) proteasome inhibition; (ii) topoisomerase inhibition; (iii) inhibition of fatty acid synthesis; (iv) accumulation of p53; (v) induction of cell cycle arrest; (vi) inhibition of phosphatidyl-inositol 3-kinase; or (vii) enhanced expression of c-fos and c-myc (Brusselmans et al, 2005). Aydin et al (2013) indicated that α-pinene is neither genotoxic nor mutagenic on healthy neurons or N2a NB cells and demonstrates that pure α-pinene possesses weak antioxidant and cytotoxic activity in cultured primary rat neurons. In addition, pure α-pinene has weak antioxidant properties and little anticancer potential on rat N2a NB cell line and suggests that α-pinene is of a limited therapeutic use as an anticancer agent.…”
Section: In Vitro Antiproliferative and Cytotoxic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to oxidative stress, previous studies reported that different mechanisms have been linked to plant products' cytotoxicity, including: (i) proteasome inhibition; (ii) topoisomerase inhibition; (iii) inhibition of fatty acid synthesis; (iv) accumulation of p53; (v) induction of cell cycle arrest; (vi) inhibition of phosphatidyl-inositol 3-kinase; or (vii) enhanced expression of c-fos and c-myc (Brusselmans et al, 2005). Aydin et al (2013) indicated that α-pinene is neither genotoxic nor mutagenic on healthy neurons or N2a NB cells and demonstrates that pure α-pinene possesses weak antioxidant and cytotoxic activity in cultured primary rat neurons. In addition, pure α-pinene has weak antioxidant properties and little anticancer potential on rat N2a NB cell line and suggests that α-pinene is of a limited therapeutic use as an anticancer agent.…”
Section: In Vitro Antiproliferative and Cytotoxic Activitymentioning
confidence: 99%
“…The observed antioxidant potential should be attributed to the phenolic oil constituents, while the oil chemoprotective efficacy against oxidative stress-mediated disorders is mainly due to its free radical scavenging properties. Recent studies have demonstrated that α-pinene (2,6,6-tri-methyl-bicyclo [3.1.1] hept-2-ene), the main component in Egyptian juniper, is present naturally in the essential oils of many aromatic plants and has antioxidant properties according to DPPH radical, hydroxyl radical, superoxide anion, malonaldehyde and β-carotene bleaching methods (Aydin et al, 2013). α-pinene was reported tohave a broad spectrum of biological activities, i.e.…”
Section: Antioxidative Activitymentioning
confidence: 99%
“…At a low exposure level, α-pinene is an effective bronchodilator and can be used for asthma treatment. Experimental studies also indicate that it exhibits antioxidant and antimicrobial activities [6,7]. It exhibits anticancer activities via distinct molecular mechanisms, i.e., the regulation of cancer cell cycle regulation, antioxidation, the reduction of inflammation, and the induction of cell apoptosis [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in accordance with previous study, which has reported that α-pinene as the major components in Cypress essential oil demonstrated strong cytotoxicity towards rat brain cancer cell line (N2a neuroblastoma cells). Significant decreases were observed in N2a cells at 100, 200 and 400 μg mL -1 (Aydin et al, 2013). Also, Matsuo et al (2011) revealed that α-pinene was able to induce apoptosis evidenced by early disruption of the mitochondrial potential, production of reactive oxygen species, and increase in caspase-3 activity in B16F10 murine melanoma cell.…”
Section: In Vivo Anticancer Activitymentioning
confidence: 91%